PEMANFAATAN AZOLLA SEBAGAI SUMBER PAKAN PADA BUDIDAYA SISTEM GANDA AZOLLA-LELE - Sudadi, Sudadi; Suryono, Suryono (Universitas Sebelas Maret, 2016)
Catfish farming is strongly influenced by the high price of feed, while azolla is a water fern that has a high nutritional value, can develop quickly and preferably by catfish as feed. The research aims to obtain the most appropriate combination treatment of Azolla inoculum dose and catfish seed size in dual system Azolla - catfish, which is able to provide the highest catfish yield. The experiments were performed in catfish ponds in completely randomized design (CRD) two factors, i,e azolla inoculum doses (250, 500 and 750 gm-1) and head circumference size of catfish seed (3, 4 and 5 cm). Dose of catfish seed is 2,000 head / m2. Variables observed were azolla fresh weight and catfish fresh weight at harvest. Azolla inoculum and catfish seed deployed together in catfish ponds and feeding with concentrate feed for one month. Azolla and catfish harvesting is done on the same day using a sieve. Once drained, Azolla and catfish were weighed separately to determine the severity. Data were analyzed by F test at the level of 95%, followed by Duncan's multiple range test (DMRT) if any significance influence. The results showed that the higher the azolla inoculum number, the higher azolla yield. The larger the size of catfish seed the higher catfish consumption to Azolla. Catfish seed size more than 4 cm will cause an imbalance between the speed of consumption of Azolla by the catfish and the azolla growth rate, so that Azolla be devoured by catfish.